Giant hiatal hernia: a clinical case - Cuevas Cisneros , Jimy Williams (2023)
Giant hiatal hernia is a condition in which more than 30 % of the stomach is displaced upward toward the thorax, thusproducing an abnormal protrusion above the diaphragmatic clamp. This can occur by various mechanisms such as alterationsat the gastroesophageal junction or diaphragmatic atrophy that can take place due to a number of reasons, includinginvolutional changes, extensive trauma or damage to the phrenic nerve.Most cases are usually asymptomatic; however, when clinical manifestations occur, they vary depending on the size of theherniation and range from chest pain (also epigastric pain), nausea, vomiting to abdominal distension. In case of presentingcomplications such as gastric volvulus or Cameron lesions, the symptoms include Borchardt’s triad, which consists ofabdominal pain and distension, violent vomiting and difficulty passing a nasogastric tube.We present the case of an 82-year-old male patient who was admitted to the emergency room for severe abdominal pain,severe hematemesis and sensory disorder. On physical examination, pale facies and diaphoresis were observed; on palpation,the main indication was abdominal pain in the epigastric area. Emergency endoscopy was requested, finding a deep ulcerwith congestive edges and active bleeding in the lower portion of the esophagus, in addition to observing that part of thegastric fundus and the cardias were herniated toward the thorax. This confirmed the diagnosis of a giant hiatal hernia;however, the treatment was interrupted by the patient when he asked for voluntary discharge after refusing to undergosurgery.